PENINGKATAN HASIL BELAJAR SISWA MELALUI MODEL KOOPERATIVE LEARNING TIPE NHT DIKELAS VIII SEMESTER I T.A 2022/2023 DI SMPN 3 TILATANG KAMANG - Nur Aini Fitri; Aniswita Aniswita; Maikartini Maikartini (Universitas Pahlawan Tuanku Tambusai, 2022)
Students achieve KKM on mathematics learning outcomes. That is, in Cycle 1, there were 9 students who reached 70 or more, and in Cycle 2, up to 13 students reached 70. Based on the learning conducted at SMPN 3 Tilatang Kamang, class VIII's mathematics learning achievement is still low. This is because the teacher does not use group learning. The motive of this study was to discover whether or not the software of the